2010
DOI: 10.1128/jb.01683-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Acetyltransferase Activity on the Thermostable Protein ST0452 from Sulfolobus tokodaii Strain 7

Abstract: and UTP in the presence of the ST0452 protein revealed that this protein possesses the GlcN-1-P-specific acetyltransferase activity. In addition, analyses of substrate specificity showed that acetyltransferase activity of the ST0452 protein is capable of catalyzing the change of galactosamine-1-phosphate (GalN-1-P) to N-acetyl-D-galactosamine-1-phosphate (GalNAc-1-P) as well as GlcN-1-P and that its sugar-1-P NTase activity is capable of producing UDP-GalNAc from GalNAc-1-P and UTP. This is the first report of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Our investigations to date have shown that the ST0452 protein exhibits high thermostability, Glc-1-P TTase activity as predicted, and unexpectedly high N-acetyl-Dglucosamine-1-phosphate uridyltransferase (GlcNAc-1-P UTase) activity ( Fig. 1) as well as amino-sugar-1-phosphate acetyltransferase (amino-sugar-1-P AcTase) activity (4,5). Comparison of the activities of the ST0452 protein to those of similar enzymes from bacteria showed that both the apparent K m and k cat values of the ST0452 GlcNAc-1-P UTase activity were smaller than those of Escherichia coli GlmU (EcGlmU) enzymes (6,7).…”
supporting
confidence: 65%
“…Our investigations to date have shown that the ST0452 protein exhibits high thermostability, Glc-1-P TTase activity as predicted, and unexpectedly high N-acetyl-Dglucosamine-1-phosphate uridyltransferase (GlcNAc-1-P UTase) activity ( Fig. 1) as well as amino-sugar-1-phosphate acetyltransferase (amino-sugar-1-P AcTase) activity (4,5). Comparison of the activities of the ST0452 protein to those of similar enzymes from bacteria showed that both the apparent K m and k cat values of the ST0452 GlcNAc-1-P UTase activity were smaller than those of Escherichia coli GlmU (EcGlmU) enzymes (6,7).…”
supporting
confidence: 65%
“…Bacteria-secreted β-lactamase can be activated under various stresses and provides multi-resistance against β-lactam antibiotics (such as ampicillin) by breaking the drug's structure and deactivating the antibacterial properties [20]. Similarly, aminoglycoside bactericidal antibiotics such as kanamycin can be modified by a group of acetyltransferases via acetylation, leading to drug inactivation [21]. Both enzymes have also been shown to be stimulated by heavy metals [26,36].…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of acetyltransferase, 10 µg protein was mixed with 2 mM acetyl-CoA and 2 mM amino sugar in 150 µl of 50 mM Tris-HCl at 80 °C for 30 min. After that, 0.5 mM DTNB in 50 µl of 50 mM Tris-HCl was added for 5 min following detection of absorbance at 410 nm [21].…”
Section: Measurement Of β-Lactamase and Acetyltransferase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the thermophilic archaeon Sulfolobus tokodaii, the ST0452 protein (20) was originally detected as a glucose-1-phosphate (Glc-1-P) thymidylyltransferase (TTase) by a similarity search within the genomic data (21). Functional analyses of the recombinant ST0452 protein produced in Escherichia coli indicated that the protein exhibited both multiple sugar-1-P nucleotidylyltransferase (NTase) activities, including N-acetylglucosamine-1-phosphate (GlcNAc-1-P) uridyltransferase (UTase) and Glc-1-P UTase activities, and multiple amino-sugar-1-P acetyltransferase activities, including glucosamine-1-phosphate acetyltransferase and galactosamine-1-phosphate acetyltransferase activities (20,22,23).…”
mentioning
confidence: 99%